2005
DOI: 10.1007/s11010-005-0821-5
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of fractionated extracts of rhizomes of high-altitude Podophyllum hexandrum: Role in radiation protection

Abstract: Whole extract of rhizomes of Podophyllum hexandrum has been reported earlier by our group to render whole-body radioprotection. High-altitude P. hexandrum (HAPH) was therefore fractionated using solvents of varying polarity (non-polar to polar) and the different fractions were designated as, n-hexane (HE), chloroform (CE), alcohol (AE), hydro-alcohol (HA) and water (WE). The total polyphenolic content (mg% of quercetin) was determined spectrophotometrically, while. The major constituents present in each fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 39 publications
4
32
0
Order By: Relevance
“…With a view to gaining an insight into the mechanisms involved in induction of apoptosis, and to explain the enhanced value of cell proliferation observed in mice treated with drug, we investigated the effect of REC-2000 on the antiapoptotic protein Bcl-2, an oncoprotein, which is known to play an important role in regulation of apoptosis. 30 The increased expression of Bcl-2 further strengthens our hypothesis that the active constituents of P. hexandrum, with reported antioxidant ability in the aqueous as well as lipid phase, [31][32][33][34] induce gene expression of Bcl-2 to prevent a large-scale progenitor cell death mediated by the radiation-induced apoptotic pathway. The difference in expression of Bcl-2 in the case of the 10 Gy group as compared to control was nonsignificant because the levels were determined at 2 hours postirradiation and at this time point reflect only the constitutive levels.…”
Section: Discussionsupporting
confidence: 68%
“…With a view to gaining an insight into the mechanisms involved in induction of apoptosis, and to explain the enhanced value of cell proliferation observed in mice treated with drug, we investigated the effect of REC-2000 on the antiapoptotic protein Bcl-2, an oncoprotein, which is known to play an important role in regulation of apoptosis. 30 The increased expression of Bcl-2 further strengthens our hypothesis that the active constituents of P. hexandrum, with reported antioxidant ability in the aqueous as well as lipid phase, [31][32][33][34] induce gene expression of Bcl-2 to prevent a large-scale progenitor cell death mediated by the radiation-induced apoptotic pathway. The difference in expression of Bcl-2 in the case of the 10 Gy group as compared to control was nonsignificant because the levels were determined at 2 hours postirradiation and at this time point reflect only the constitutive levels.…”
Section: Discussionsupporting
confidence: 68%
“…25 However, recently, the radioprotective properties of P hexandrum have been discovered and established in our institute. [14][15][16][17][18][19][20][21][22][23][24] In the present study, a phytochemically characterized fraction of P hexandrum (REC-2006), containing podophyllotoxin and its derivatives (4′-demethyl podophyllotoxin-b-D glucopyranoside etc) 19 was used to evaluate the radioprotective efficacy in hepatoma cell lines having different p53 status. Observations of the present study indicated that the cytotoxic and proliferative effect of REC-2006 is independent of the p53 status of the cell lines as both p53-positive and p53-negative cell lines exhibit the median lethal concentration (LC Varied concentration ranges (10 -3 to 10 -7 mg/mL) of REC-2006 and treatment times (0.5, 1, 1.5, 2, and 2.5 h) were used to achieve maximum radioprotective efficacy in both the cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings show that REC-2006 renders significant (P < .05) protection in the wild type functional p53 carrying cell line as compared with the p53 null cell line when administered 2 h before exposure to acute IR. Even though the radioprotective properties of P hexandrum were investigated earlier and established in our institute, [14][15][16][17][18][19][20][21][22][23][24] the present observations further open the window for use of REC-2006 as a radioprotector during planned radiation exposures (rescue operation as well as in radiotherapy of tumor cells) because it is well known that more than 60% of the tumor has cells with mutated/nonfunctional p53 protein, which is otherwise required for regulation of downstream genes responsible for cell cycle regulation and DNA repair. Our results indicate a potential for differential radioprotection of p53-expressing cells and p53-deficient cells, particularly during radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…They include free radical scavenging, apoptosis and cell cycle related activities in in vitro (Hep G2 cells) as well as in vivo models [42][43][44]. Chawla et al worked on radioprotective properties of this plant and told the effect of variation in aryltetralin [45,46]. Some properties of this plant were also studied and compared by Arora et al who worked on antioxidant and radioprotective properties of P. hexandrum growing at high altitude as well as low altitudes and then compared both of them [41].…”
Section: Radioprotective Efficacymentioning
confidence: 99%